2004
DOI: 10.1002/pssc.200303942
|View full text |Cite
|
Sign up to set email alerts
|

Optical quality improvement of InGaAs/AlAs/AlAsSb coupled double quantum wells grown by molecular beam epitaxy

Abstract: Intersubband optical transitions at short wavelengths in strain-compensated In 0.70 Ga 0.30 As-AlAs double quantum wells are investigated by means of mid-infrared absorption. Trade-offs between achieving a high transition energy and a large oscillator strength of the two highest-energy intersubband transitions using our strain-compensation approach are analyzed as a function of the widths of the two wells. Two design strategies leading to relatively strong intersubband optical transitions at 800 meV, 1.55 m, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We also demonstrated that the absorption response time was greatly reduced to 690 fs when InGaAs/AlAs/ AlAsSb coupled double quantum wells (C-DQWs) were used [6]. Our most recent study indicates that the application of AlAs diffusion-stopping layers to C-DQWs significantly improves ISBT properties with respect to both Is and response time [7,8]. However, this sample had many cross-hatched lines and its X-ray diffraction (XRD) rocking curve had broad satellite peaks.…”
Section: Introductionmentioning
confidence: 91%
“…We also demonstrated that the absorption response time was greatly reduced to 690 fs when InGaAs/AlAs/ AlAsSb coupled double quantum wells (C-DQWs) were used [6]. Our most recent study indicates that the application of AlAs diffusion-stopping layers to C-DQWs significantly improves ISBT properties with respect to both Is and response time [7,8]. However, this sample had many cross-hatched lines and its X-ray diffraction (XRD) rocking curve had broad satellite peaks.…”
Section: Introductionmentioning
confidence: 91%